Theoretical investigation of optical phenomenon from nanometric antireflex layers. Issue 1 (December 2020) - Pascu, A T; Pascu, M A; Besnea, D
Summary: Within the paper were studied the physical phenomenon which characterize the passing of light through a dielectric environment, a case which can be applied to eyeglass lenses with a nanometric antireflex layer. Were determined the optical characteristics required or such nanometric layers. Was studied practically the increase of light transmission, respectively the reduction of reflection for this new manufacturing technology for eyeglass lenses and the nanometric antireflex layers. The study was completed with photometric measurements and measurements for the resistance of the antireflex coatings compared for several manufacturing technologies.